Trans fatty acids content in cakes, muffins and pastries from samples with brand and non-brand names - Siti Nurshabani Salleh.
High trans fatty acids (TFA) intake can cause adverse changes in blood lipids based on many epidemiological studies. The major sources of TFA in human diet come from bakery products such as cakes, cookies, muffins, breads and pastries. This study was carried out to determine TFA content in cakes, muffins and pastries. Two different type of samples were selected which are with brand name and with no brand name bakery samples that were purchased from local bakery shops and night market in Seri Kembangan, Selangor. For brand bakery samples, the cakes, muffins and pastries were selected and analyzed. Each of these samples contains three different types. The total number samples with brand bakery samples with brand bakery samples were nine. The same goes to with non-brand bakery samples. So, the total number of samples selected and analyzed was eighteen. Total fat content was determined by Soxhlet method, meanwhile TFA content was determined by using gas chromatography. Results were expressed as percentage of total fat, percentage of total TFA content per 100g food and percentage of total TFA content per 100g lipid. Results showed that there were significant differences (p<0.05) in total fat content within brand and non-brand bakery samples. Higher fat content were observed in brands cakes selected (34.5% - 36.2%). There are significant differences (p<0.05) in total TFA content in 100g food within brand and non-brand samples selected. The results also showed that there are significant differences (p<0.05) in total TFA content per 100 g food between brand and non-brand samples selected. The TFA content per 100g food were observed higher in non-brand cheese cake (8.36%) were the lowest in chocolate cake with brand (2.26%). The result showed that there were no significant differences (p>0.05) total trans fatty acid contents in 100g lipid between samples with brand and sample with no-brand name. In conclusion, this study shown that the content of TFA in the various bakery samples were high exceeded the recommended TFA content in food by World Health Organization, 2003. The intake of these bakery samples should be less than 50g per day and taken consciously to avoid high TFA intake. This study has detected significant differences in total amount of TFA contents in brand and non-brand bakery samples.